Kajian Potensi Produksi Hijauan Pakan pada Lahan Eksisting dan Potensial untuk Meningkatkan Populasi Ternak Ruminansia di Kabupaten Aceh Besar - Mira Delima; Abubakar Karim; M. Yunus (Jurnal Agripet, 2015)
(The study of prospective forage production on existing and potential land use to support increasing livestock population in Aceh Besar)ABSTRACT. The purpose of this research was to find out the width and scattered location of existing land use which its land capability class suitable for pastures; forage production prospective, and land carrying capacity. The combination of survey and evaluation method was used in this study. The primary data were obtained by field observation and compiling documents, while the secondary data were obtained from various sources, including Bappeda Aceh, and Dinas Peternakan Aceh Besar. Land capability classification was defined based on a modified USDA method and land capability class mapping was prepared based on overlay method by geoprocessing of Geographic Information Systems. The attributes delineating land capability classification included slope, erosion potential and soil depth. Spatial and attributes data were processed using ArcGIS 9.3. Interpretation of land use map derived from satellite imagery analysis results. Brachiaria humidicola green production (tons/year) was determined by assumption-based on obtaining data from various sources. Present livestock population and increasing of population target up to 2017 were obtained from Dinas Peternakan Aceh Besar. The results showed that the existing land use area was 28,632.23 ha (59.03 %), whereas the potential land use area was 19,875.73 ha (40.97%). Land use area for pastures in the district of Aceh Besar, both existing and potential, were sufficient to support the achievement of livestock population increasing program.